Biotremology: Do physical constraints limit the propagation of vibrational information?. (August 2017) - Mortimer, Beth
Abstract : Vibrations are a ubiquitous source of information in the environment, and are utilized by a wide range of animals. In this review, I concentrate on the propagation of vibrations across and through substrates, which are materials and surfaces. During the propagation process, physical constraints act on vibrational signals and cues, including loss of energy, filtering or distortion of information. An understanding of these physical mechanisms is important for answering biological questions about communication and information gathering, particularly the reach of signals/cues and how information can be separated from background noise. In this review, I explore the interdisciplinary links central to the field of biotremology to probe the extent to which physical laws limit information propagation. In what follows, I start with a primer in wave theory, before focusing on how the physical factors of wave type and substrate properties affect vibration propagation. I then turn to the interacting biological factors that influence signal/cue propagation during animal-substrate coupling, discussing the numerous behavioural and morphological adaptations employed to mitigate physical constraints. Following this, I then move from limits to possibilities, discussing how animals harness physical laws to provide useful information. Using examples from a wide range of animal systems and biological contexts, I highlight the array of evolutionary strategies to promote the propagation of information given inevitable physical constraints. Highlights: Vibrations through substrates contain information important for many species. Complex physical constraints act on propagating vibrations. Adaptations of animals can mitigate the effect of these constraints. Animals can also use physical laws to gain information.